GEOGRAFIYA DARSLARIDA ROLLI O‘YINLARDAN FOYDALANIB O‘QUVCHILARDA FANGA OID KOMPETENSIYALARNI SHAKLLANTIRISH METODIKASI (“Inson faoliyati muhim ekologik omil sifatida” mavzusi misolida) - Xalilov, X.B. (SCIENCE and SOCIETY, 2021)
In this article, the use of role-playing games in the teaching of "Human activity as an important environmental factor" in the lessons of geography in the upper grades of secondary schools has a positive effect on the formation of knowledge, skills, abilities and general and scientific competencies. shown to do.
Keywords: “Game” concept; game phenomenon; role play; environmental culture; defendant; defender; accuser; ecosystem; statistics; biosphere; judge; human